Label-free, all-optical detection, imaging, and tracking of a single protein - Arroyo, J; Andrecka, J; Spillane, KM; Billington, N; Takagi, Y; Sellers, JR; Kukura, P (American Chemical Society, 2014)
Optical detection of individual proteins requires fluorescent labeling. Cavity and plasmonic methodologies enhance single molecule signatures in the absence of any labels but have struggled to demonstrate routine and quantitative single protein detection. Here, we used interferometric scattering microscopy not only to detect but also to image and nanometrically track the motion of single myosin 5a heavy meromyosin molecules without the use of labels or any nanoscopic amplification. Together with the simple experimental arrangement, an intrinsic independence from strong electronic transition dipoles and a detection limit of <60 kDa, our approach paves the way toward nonresonant, label-free sensing and imaging of nanoscopic objects down to the single protein level.